The role of MLH1, MSH2 and MSH6 in the development of colorectal cancer in Uganda - Richard Wismayer; Rosie Matthews; Celina Whalley; Julius Kiwanuka; Fredrick Elishama Kakembo; Steve Thorn; Henry Wabinga; Michael Odida; Ian Tomlinson (BMC Cancer)
Abstract Introduction In Uganda, colorectal cancer (CRC) is steadily increasing according to the Kampala Cancer Registry. In the West, microsatellite instability is detected in 90% of hereditary nonpolyposis colon cancers (HNPCC) which account for 1–2% of all CRC, and 15% of sporadic CRC. Germline mutations in MLH1 and MSH2 account for 90% of HNPCC in the West, whilst the remainder of cases are due to mutations in MSH6 and PMS2. The aim of this study was to determine the microsatellite instability (MSI) status and determine the proportions of MLH1, MSH2, and MSH6 pathological mutations in Ugandan CRC patients. Methodology This was a cross-sectional study carried out between 1st January 2008 to 15th September 2021. Patients were recruited prospectively from 16th September 2019 to 16th September 2021, from Masaka Regional Referral Hospital, Mulago National Referral Hospital, Uganda Martyrs’ Hospital Lubaga and Mengo Hospital. From 1st January 2008 to 15th September 2019, CRC FFPE tissue blocks were obtained from the archives of the Department of Pathology, Makerere University. Data was abstracted from the medical case files for demographics, topography and stage. The histopathological subtype and grade of CRC were obtained by two consultant pathologists from the H&E slides. DNA was extracted from CRC formalin-fixed paraffin-embedded (FFPE) tissue blocks. Library preparation was completed using the Qiagen custom design panel. The custom panel represented 56 genes. The MLH-1, MSH2, MSH6, BRAF and KRAS genes were sequenced using the above library preparation and NGS sequencing. The MSI status was obtained if one of the MSI genes, MLH1, MSH2 or MSH6 was pathologically mutated. If none of the genes was pathologically mutated it was considered MSI negative, microsatellite stable (MSS). Immunohistochemistry was carried out to determine whether MLH1 and PMS2 was MMR proficient or deficient. Categorical data was summarized using frequencies and proportions corresponding to each of the three histopathological subtypes and MSI status subtypes. Continuous and categorical variables were analyzed using the chi-square and Fischer’s exact tests. A p -value ≤ 0.05 was considered statistically significant for all the analyses. Results Out of 127 CRC patients, the mean(SD) age of MSI cases was 55.6(16.9) years and of MSS cases was 55.4(15.5) years. The majority were MSS, 75(59.06%) followed by MSI, 52(40.9%). There were 14(11.02%) MLH-1 mutations, 30(23.62%) MSH2 mutations, and 26(20.47%) MSH6 mutations. BRAF mutational analysis showed only 5(3.9%) having pathologic missense BRAF V600 mutations. KRAS mutations consisted of only 8(6.3%) having pathologic missense KRAS mutations. Conclusions The high rate of MSI in Ugandan colorectal tumours was mainly associated with a lack of BRAF mutations and a high frequency of MSH2 and MSH6 MMR gene mutations. In CRC patients, identification of the causative mutation is recommended, however in a resource-limited setting, MSI testing and immunohistochemistry is more cost effective. In Ugandan CRC patients who meet at least one of the Bethesda criteria, MSI testing and immunohistochemistry may therefore be offered to obtain the MSI status of the tumour.